Effects of complex internal structures on rheology of multiple emulsions particles in 2D from a boundary integral method - Wang, Jingtao; Liu, Jinxia; Han, Junjie; Guan, Jing (Physical review letters, 2013)
A boundary integral method is developed to investigate the effects of inner droplets and asymmetry of internal structures on rheology of two-dimensional multiple emulsion particles with arbitrary numbers of layers and droplets within each layer. Under a modest extensional flow, the number increment of layers and inner droplets, and the collision among inner droplets subject the particle to stronger shears. In addition, the coalescence or release of inner droplets changes the internal structure of the multiple emulsion particles. Since the rheology of such particles is sensitive to internal structures and their change, modeling them as the core-shell particles to obtain the viscosity equation of a single particle should be modified by introducing the time-dependable volume fraction Φ(t) of the core instead of the fixed Φ. An asymmetric internal structure induces an oriented contact and merging of the outer and inner interface. The start time of the interface merging is controlled by adjusting the viscosity ratio and enhancing the asymmetry, which is promising in the controlled release of inner droplets through hydrodynamics for targeted drug delivery.